Polymer Composites Review of Natural Fiber Reinforced Polymer Composites - Nguong, C.W.; Lee, S.N.B.; Sujan, Debnath (School of Engineering & Science, Curtin University Sarawak Campus, 2012)
Renewable natural fibers such as oil palm, flax, and pineapple leaf can be utilized to obtain new high performance polymer materials. The reuse of waste natural fibers as reinforcement for polymer is a sustainable option of replacing or reducing traditional synthesis fibers utilized in industry. However, the natural fibers due to its high hydroxyl content of cellulose are susceptible to absorb water that affects the composite mechanical properties. Research found that nano materials such as nano Silica Carbide (n-SiC) and nano Clay can add into the polymer composite to overcome this problem by enhancing its mechanical properties in wet condition. The addition of nano material improves the tensile and wear properties, flexural stress-strain behavior, fracture toughness, and fracture strength of polymer natural composites in wet and dry conditions.